The Processing Times and the Satisfaction of Workers Involved in the Execution of Expenditures: the Case of a Peruvian Public University - Arnao Rondán, Raymundo I. (Revista del CLAD Reforma y Democracia, 2023)
According to the stated objectives, this research shows a positive correlation between job satisfaction of employees involved in the budget execution procedures of a public university and the level of knowledge of their functions and the basic regulations concerning these procedures. It also provides information on the procedures and times of expenditure execution at the university and its possibilities for improvement. To measure of budget execution times, the types and number of procedures carried out in 2021 were identified at the university. Then, based on this data, a stratified sample of 539 cases was determined for measurement. To calculate the other variables outlined in the research objectives, a survey was developed with two sets of questionnaires applied to those directly involved in the process: one to measure the knowledge of their functions and the basic regulations concerning the budget execution, and the other to determine their job satisfaction. In addition, feedback and validation sessions were held to identify variables and their measurement instruments with the stakeholders of the institution under study. The results show that the institution’s expenditure execution processing times can be substantially reduced, depending mainly on the decision of its managers to convene and lead the necessary improvements. On the other hand, an average level of knowledge of their functions and of the basic regulations of the budget execution was identified among the employees involved in this procedure. It was also found that the university’s management tools are not a significant source of knowledge for the employees, implying a weak institutional mediation in providing this knowledge. In this context, it is suggested a greater organizational intervention to provide knowledge and enhance job satisfaction among employees involved in the budget execution, for the benefit of the university community.
Keywords: Budget Administration; Expenditures Administration; Occupational Profile; Job Satisfaction; Universities; Surveys; Case Analysis; Peru